2020
DOI: 10.4251/wjgo.v12.i6.642
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnosis and management of pancreatic mucinous cystadenoma and cystadenocarcinoma: Single-center experience with 82 patients

Abstract: BACKGROUND Mucinous cystic neoplasm (MCN) of the pancreas is characterized by mucin-producing columnar epithelium and dense ovarian-type stroma and at risk for malignant transformation. Early diagnosis and treatment of MCN are particularly important. AIM To investigate the clinical characteristics of and management strategies for pancreatic mucinous cystadenoma (MCA) and mucinous cystadenocarcinoma (MCC). METHODS The clinical and pathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Nevertheless, we identified that serum CA125 was more likely a predictor of advanced MCN than advanced IPMN. The results were similar to those of two recently published studies[ 25 , 26 ]. The possible reason may be the tissue histogenesis of MCN.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, we identified that serum CA125 was more likely a predictor of advanced MCN than advanced IPMN. The results were similar to those of two recently published studies[ 25 , 26 ]. The possible reason may be the tissue histogenesis of MCN.…”
Section: Discussionsupporting
confidence: 92%
“…Postlewait et al retrospectively identified 349 patients with MCN and demonstrated that patients with malignant neoplasms had a higher serum CA19-9 level than those without (median, 210 vs. 15 U/ml, P=0.001) ( 5 ). Zhao et al ( 17 ) showed that serum CA19-9 levels were significantly higher in malignant MCNs than in benign MCNs patients (P=0.026) for resected MCNs. Our study is consistent with previous findings, which finds that the serum levels of CA19-9 in the high grade and invasive group (309.2±423.2 U/ml) was significantly higher than those in the low/moderate grade group (49.0±198.3 U/ml, P=0.050), with an area under the ROC curve of 0.68.…”
Section: Discussionmentioning
confidence: 99%
“…However, cyst fluid CEA has limited role in predicting malignancy or radiographic progression mucinous cysts of the pancreas (18). Several studies have also determined circulating CEA in predicting malignant MCNs (14,16,17). For example, Zhao et al (17) demonstrated that serum CEA levels were significantly higher in malignant MCNs than in benign MCNs patients (P=0.005) for 82 patients with resected MCNs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serous cystadenomas are rare glycogen-rich lesions, which arise from pancreatic ductal epithelium (10). But mucinous cystadenomas are cystic epithelial tumors, consisting of ovarian stromata and mucus-producing columnar epithelium (11). In clinical practice, most pancreatic cystadenoma patients are asymptomatic or manifest non-specific symptoms (12).…”
Section: Introductionmentioning
confidence: 99%